Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Trả lời :
a)\(-\frac{3}{5}+\frac{9}{16}+-\frac{2}{5}+\frac{7}{16}\)
=\(\left(-\frac{3}{5}+-\frac{2}{5}\right)+\left(\frac{9}{16}+\frac{7}{16}\right)\)
=\(-1+1\)
=\(1\)
b)\(5\frac{2}{3}-1\frac{1}{5}-2\frac{2}{3}\)
=\(\left(5-1-2\right)\left(\frac{2}{3}-\frac{1}{5}-\frac{2}{3}\right)\)
=\(-2\frac{1}{5}\)
Hok_Tốt
#Thiên_Hy
a ) -3/5 + 9/16 + (-2/5 ) + 7/16
[ -3/5 + (-2/5) ] + (9/16 + 7/16 )
-1 + 1
0
b) 5 2/3 - 1 1/5 - 2 2/3
(5 2/3 - 2 2/3) - 1 1/5
3 - 6/1
-3
Câu a )
\(-\frac{3}{5}+\frac{9}{16}+-\frac{2}{5}+\frac{7}{16}=\left(-\frac{3}{5}+-\frac{2}{5}\right)+\left(\frac{9}{16}+\frac{7}{16}\right).\)
\(=\left(-1\right)+1=0\)
hk tốt !
\(\frac{6}{11}\cdot\frac{3}{14}+\frac{-5}{16}+\frac{3}{14}\cdot\frac{5}{11}+\frac{-3}{16}\)
\(=\frac{6}{11}\cdot\frac{3}{14}+\frac{3}{14}\cdot\frac{5}{11}+\frac{-5}{16}+\frac{-3}{16}\)
\(=\frac{3}{14}\cdot\left(\frac{6}{11}+\frac{5}{11}\right)+\left(\frac{-5}{16}+\frac{-3}{16}\right)\)
\(=\frac{3}{14}\cdot\frac{6+5}{11}+\frac{-5+\left(-3\right)}{16}\)
\(=\frac{3}{14}\cdot\frac{11}{11}+\frac{-8}{16}\)
\(=\frac{3}{14}\cdot1+\frac{-1}{2}\)
\(=\frac{3}{14}+\frac{-1}{2}\)
\(=\frac{3}{14}+\frac{-7}{14}\)
\(=\frac{3+\left(-7\right)}{14}\)\(=\frac{-4}{14}=\frac{-2}{7}\)
\(\frac{-5}{6}+\left(7x-\frac{1}{2}\right)\cdot\frac{2}{9}=-1\frac{1}{3}\)
\(\frac{-5}{6}+\frac{14}{9}\cdot x-\frac{1}{9}=-\frac{4}{3}\)
\(\frac{14}{9}\cdot x-\frac{1}{9}=-\frac{4}{3}+\frac{5}{6}\)
\(\frac{14}{9}\cdot x-\frac{1}{9}=-\frac{1}{2}\)
\(\frac{14}{9}\cdot x=-\frac{1}{2}+\frac{1}{9}\)
\(\frac{14}{9}\cdot x=-\frac{7}{18}\)
\(x=-\frac{7}{18}:\frac{14}{9}\)
\(x=-\frac{1}{4}\)
a, 1 x 2 x 3 x ... x 8 x 9 - 1 x 2 x 3 x ... x 8 - 1 x 2 x 3 x ... x 7 x 8 x 8
= 1 x 2 x 3 x ... x 8 ( 9 - 1 - 8 ) = 1 x2 x 3 x ... x 8 . 0 = 0
1 .
[ 6 + ( 1/2 ) 3 - /-0,5/ ] : 3/12
= [ 6 + 1/8 - ( -5/10 ) ] . 12/3
= [ 6 + 1/8 + 5/10 ] .4
= [ 6 + 1/8 + 1/2 ] .4
= [ 48/8 + 1/8 + 4/8 ] .4
= 53/8 . 4
= 53 . 1/2
= 53/2
2.
1/3 + 5/4 : (-35/16)
= 1/3 + 5/4 . ( 16/-35 )
= 1/3 + 1 . 4/4 . (-7 )
= 1/3 + 4/28
= 1/3 + 1/7
= 7/21 + 3/21
= 10/21
3 .
11 3/13 - ( 2 4/7 + 5 3/13 )
= 11 3/13 - 2 4/7 - 5 3/13
= { [ ( 11 - 5 ) . ( 3/13 - 3/13 ) } - 2 4/7
= ( 6 . 0 ) - 2 4/7
= 0 - 18/7
= 18/7
4 .
1 3/7 + (-1/3 + 2 4/7 )
= 1 3/7 + ( -1 )/3 + 2 4/7
={ [ ( 1 + 2 ) . ( 3/7 + 4/7 ) } + ( -1 )/3
= ( 3 . 1 ) + ( -1 )/3
= 3 + ( -1 )/3
= 9/3 + ( -1 )/3
= 8/3
5 .
( 6 4/9 + 3 7/11 ) - 4 4/9
= 6 4/9 + 3 7/11 - 4 4/9
= { ( 6 - 4 ) . ( 4/9 - 4/9 ) } + 3 7/11
= ( 2 . 0 ) + 3 7/11
= 0 + 40/11
= 40/11
Nếu đúng thì k cho mình nha !
a) Ta có: \(\left|5\cdot0.6+\dfrac{2}{3}\right|-\dfrac{1}{3}\)
\(=\left|3+\dfrac{2}{3}\right|-\dfrac{1}{3}\)
\(=3+\dfrac{2}{3}-\dfrac{1}{3}\)
\(=3+\dfrac{1}{3}=\dfrac{10}{3}\)
b) Ta có: \(\left(0.25-1\dfrac{1}{4}\right):5-\dfrac{1}{5}\cdot\left(-3\right)^2\)
\(=\left(\dfrac{1}{4}-\dfrac{5}{4}\right)\cdot\dfrac{1}{5}-\dfrac{1}{5}\cdot9\)
\(=\dfrac{-4}{4}\cdot\dfrac{1}{5}-\dfrac{1}{5}\cdot9\)
\(=\dfrac{1}{5}\cdot\left(-1-9\right)\)
\(=-10\cdot\dfrac{1}{5}=-2\)
c) Ta có: \(\dfrac{14}{17}\cdot\dfrac{7}{5}-\dfrac{-3}{17}:\dfrac{5}{7}\)
\(=\dfrac{14}{17}\cdot\dfrac{7}{5}-\dfrac{-3}{17}\cdot\dfrac{7}{5}\)
\(=\dfrac{7}{5}\cdot\left(\dfrac{14}{17}+\dfrac{3}{17}\right)\)
\(=\dfrac{7}{5}\cdot1=\dfrac{7}{5}\)
d) Ta có: \(\dfrac{7}{16}+\dfrac{-9}{25}+\dfrac{9}{16}+\dfrac{-16}{25}\)
\(=\left(\dfrac{7}{16}+\dfrac{9}{16}\right)-\left(\dfrac{9}{25}+\dfrac{16}{25}\right)\)
\(=\dfrac{16}{16}-\dfrac{25}{25}\)
\(=1-1=0\)
e) Ta có: \(\dfrac{5}{6}+2\sqrt{\dfrac{4}{9}}\)
\(=\dfrac{5}{6}+2\cdot\dfrac{2}{3}\)
\(=\dfrac{5}{6}+\dfrac{4}{3}\)
\(=\dfrac{5}{6}+\dfrac{8}{6}=\dfrac{13}{6}\)